Iodine intake by adult residents of a farming area in Iwate Prefecture, Japan, and the accuracy of estimated iodine intake calculated using the Standard Tables of Food Composition in Japan - Nakatsuka, Haruo; Chiba, Keiko; Watanabe, Takao; Sawatari, Hideyuki; Seki, Takako (Environmental health and preventive medicine, 2016)
Objectives Iodine intake by adults in farming districts in Northeastern Japan was evaluated by two methods: (1) government-approved food composition tables based calculation and (2) instrumental measurement. The correlation between these two values and a regression model for the calibration of calculated values was presented. Methods Iodine intake was calculated, using the values in the Japan Standard Tables of Food Composition (FCT), through the analysis of duplicate samples of complete 24-h food consumption for 90 adult subjects. In cases where the value for iodine content was not available in the FCT, it was assumed to be zero for that food item (calculated values). Iodine content was also measured by ICP-MS (measured values). Results Calculated and measured values rendered geometric means (GM) of 336 and 279 μg/day, respectively. There was no statistically significant ( p > 0.05) difference between calculated and measured values. The correlation coefficient was 0.646 ( p < 0.05). Discussion With this high correlation coefficient, a simple regression line can be applied to estimate measured value from calculated value. A survey of the literature suggests that the values in this study were similar to values that have been reported to date for Japan, and higher than those for other countries in Asia. Conclusions Iodine intake of Japanese adults was 336 μg/day (GM, calculated) and 279 μg/day (GM, measured). Both values correlated so well, with a correlation coefficient of 0.646, that a regression model ( Y = 130.8 + 1.9479 X , where X and Y are measured and calculated values, respectively) could be used to calibrate calculated values.